The Influence of Green Products and Green Prices on Loyalty and Sustainability through Consumer Satisfaction - Candra Hasbiawan; Sonny Indrajaya (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
This study aims to analyze the influence of green products and green prices on customer loyalty and sustainability with consumer satisfaction as a mediating variable. A quantitative approach was used by a survey method of 200 respondents of Sari Roti consumers in the Greater Jakarta area. The sampling technique is purposive sampling, and the data is analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4.The results of the study show that green products and green prices have a significant positive effect on consumer satisfaction. Consumer satisfaction then has a significant positive effect on customer loyalty, which ultimately has a positive impact on sustainability. Consumer satisfaction has also been proven to mediate the relationship between green products and green prices on customer loyalty and sustainability. These findings provide practical implications that companies need to focus on eco-friendly product innovation and pricing that reflects sustainability values to build consumer satisfaction and loyalty in a sustainable manner.